A new species of Eugenia subgen. Pseudeugenia (Myrtaceae) from the Atlantic Forest in the Brazilian state of Rio de Janeiro - Campelo, Marcos Vinicius; Fernandes, Thiago; Guimarães, Gabriel Silva; Maruyama, Adriano Da Silva De Cicco; Faria, Jair Eustáquio Quintino; Souza, Marcelo Da Costa; Braga, João Marcelo Alvarenga (Phytotaxa, 2025)
Eugenia pachymarginata, a new species from the Brazilian Atlantic Forest, in the state of Rio de Janeiro, is here described. The new species is here assigned to Eugenia subgen. Pseudeugenia due to its congruent morphology. It is morphologically related to E. malacantha and E. culicina. This study provides a morphological description of the new taxon, accompanied by illustrations and notes on its taxonomy, habitat, distribution and phenology. Additionally, a distribution map and a conservation assessment are presented.